Analysis of capital structure indicators and credit risk for a sample of Iraqi private commercial banks - Al_ali, Mohammed (The Gulf Economist, 2022)
The aim of the research is to analyze the capital structure indicators and credit risks and to know the relationship between them for some private commercial banks in Iraq, given the importance of commercial banks as they represent the heart of the financial system and the risks they are exposed to, the most important of which are credit risks, as these banks may be one of the direct or third reasons Direct in the occurrence of financial crises. As the financial analysis of the annual data of the study sample consisting of (10) commercial banks listed in the Iraqi Stock Exchange for the period from 2011-2020 was conducted, based on the annual reports of commercial banks, using the financial analysis ratios represented by the ratio of equity to total assets, and the ratio of total Debt to total assets and these ratios represent the capital structure. As for the credit risk indicators, it was represented by the allowance for doubtful debts to total loans, as well as the ratio of non-performing loans to total loans, and it was found that there is an inverse relationship to the capital structure if it is represented by property rights (self-financing). and credit risk, as well as the existence of an inverse relationship to the capital structure represented by debt (non-self-financing) and credit risk.